Digital Youth in Brick and Mortar Schools: Examining the Complex Interplay of Students, Technology, Education, and Change. Issue 5 (May 2015) - Peck, Craig; Hewitt, Kimberly Kappler; Mullen, Carol A.; Lashley, Carl; Eldridge, John; Douglas, Ty-Ron M. O.
Context: The past decade has witnessed a sustained emphasis on information and communication technologies (ICT) in education, coupled with the rise of online social media and increasing pervasiveness of personal media devices. Research Question: Our research question asked: How has this changing context affected the educational experiences of American high school students? Setting: The exploratory, qualitative study took place at two high schools in a large metropolitan district in the southeastern United States. One high school was in a downtown area, and the other was in a suburban setting. Research Design: The researchers used various qualitative research approaches, including interviews, on-site observations, and document analysis. Our interview participants included classroom teachers and support staff as well as students drawn from across each school's grade levels. We also shadowed 10 of the student interview participants through their entire school days. Findings: In terms of classroom instruction, we found that ICT had affected school, teacher, and student practices in some ways, but traditional teacher-centered practices such as student completion of printed worksheets were still prevalent. However, widespread student access to personal media devices and online social media site influence had a noticeable effect on the two high schools. The researchers encountered specific "types" of students whom technology particularly influenced: "Digital Rebels, " "Cyber Wanderers, " and "eLearning Pioneers." In addition, we discovered that computer-based remedial programs served as problematic educational lifelines for students at risk of dropping out. Conclusions: The two study high schools presented a complex portrait. In the end, technology functioned both as an imperfect school reform effort that produced only partial instructional change and as a successful though uninvited disruptive innovation that allowed students to challenge and unsettle existing educational norms. We close by considering implications of our findings.